Effects of plyometrics training on muscle stiffness changes in male volleyball players - Mroczek, D.; Mackala, K.; Chmura, P.; Superlak, E.; Konefal, M.; Seweryniak, T.; Borzucka, D.; Rektor, Z.; Chmura, J. (The Journal of Strength and Conditioning Research, 2019)
We investigated whether 6 weeks of specific plyometric training (PT) impacts on changes in muscle stiffness and enhances the vertical jumping ability as the indirect evaluation of the explosive power of the lower extremities of male volleyball players. Sixteen male collegiate volleyball players participated in this experiment. Regular PT was performed twice per week for 60-90 minutes each time. During each PT session, heart rate and muscle stiffness data were collected. Two series of 10 single measurements of each muscle (23 points of the front and back legs) were measured the day before the first enhanced training session and after completing each week of PT. Participants were tested for maximum effort in vertical jumping using the squat jump (SJ) with hands on thighs, countermovement jump (CMJ), and CMJ1 with a 2-step to 3-step approach. Jumping motor ability tests were completed. Data were collected 1 day before PT. The last measurement was performed 3 days after completing the last week of PT. The 6-week PT program only had an effect on the statistically relevant increase in muscle stiffness in the tibialis anterior (highest value, 593.86 ± 60.24 N/m) and quadriceps. Improvements in the explosive power of leg muscles resulted in a significant increase in the vertical jumping ability; there were improvements in SJ and CMJ (p = 0.0338 and p = 0.0007, respectively). If PT involves a moderate workload and if players never exceed the intensity target of the workout, then less muscle stiffness and muscle soreness may occur.